With Hardship Comes Ease: Muslim-feminist meditations on miscarriage, care-based knowing, and lineage - Sarah Munawar (Journal of Philosophical Investigations)
Through a critical auto-ethnographic account of miscarriage and grief, I explore what it means to inherit Islam as a tradition through care-based modes of knowing. Through Muslim-feminist theorizing, I blend Quranic narratives of care with maternal lineages of Islam I have inherited through care, that not only guide how I think about care Islamically, but also, how I practice care in my relations as a Muslim. I also illustrate the value of intertextuality of care as it is experienced across lived time, and across generations, within systems of kin and the need to let go of monolithic senses of tradition, and moral epistemology, within our practice of comparative care ethics. I draw a parallel between colonial, and white-orientated modes of knowing Muslims, and Islam, and grounded care-based modes of knowing by which we come to know and inhabit our practices of Islam in caring as, and being cared for , as Muslims.